Manual de funciones para mejorar el desempeño organizacional de la Industria Arrocera Sarmiento año 2012 - Castro Quiroz, Maryuri Eulalia (2013)
Research on the development of the Manual Functions for Human Resource Management in the Rice Industry Sarmiento, aimed to provide a document that describes and encompasses the activities that must meet each of the employees based on the assigned functions. The data collection was performed by applying research techniques, such as: the survey that was applied to the workers and employees of the administrative staff of the Rice Industry Sarmiento, in order to know the activities that each employee plays, while that the interview was applied to the Authority and the Director of the Units directly related to staff movements. The analysis of the results allowed determining the degree of compliance with the workers and employees assigned duties. Also allowed to determine whether the allocation of the functions has been based on the academic and professional profile that has each employee. In the Function Manual describes his job, a process that is to list the tasks or duties that make a charge that differentiate it from others, detailing what the occupant does, when it does, how it does and why it ago. The Handbook provides greater ease in making decisions and implementing them, so that no conflicts or leakage of responsibilities because they eliminate confusion in the tasks performed in the Administrative Unit, avoiding the introduction of any inaccuracies. Given the above, we propose the development of a manual functions Sarmiento Rice Industry, as an alternative to determine the functions that each employee must abide by the same to be allocated according to academic preparation. With which aims to fulfill the assigned tasks efficiently, effectively and efficiently, and thus optimize and transparent services provided Sarmiento Rice Industry.